Modification and effect of Blade Distance on Onion Slice thickness of Mechanical Onion Slicer - Hasimi Rafsanjani H.; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2016)
One of the unit process is slicing. This study was aimed to examine the effect of blade distance on the effective capacities,  percentage of perfect  sliced onion and percentage of left onion at mechanical slicer.The research was conducted in November 2014 to February 2015 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, using non-factorial completely randomized design(CRD). The parameters were the effective capacity of equipment and the percentage of perfect slicer, percentage of broken materials.The results showed that the effective capacity was 29,02kg/hr, 32,99kg hr and 42,14kg/hr respectively, the percentage of unsliced onion was 4,17%,4,00% and 3,17%respectively, and percentage of left onion at the mechanical slicer was 4,33%, 4,00%, 3,00% respectively. Keywords:blade, slicing, capacity.